Late-Breaking Abstracts 2020
DOI: 10.1136/jitc-2020-sitc2020.0805
|View full text |Cite
|
Sign up to set email alerts
|

805 Safety and emerging evidence of immune modulation of the live biotherapeutic MRx0518 in the neoadjuvant setting for patients awaiting surgical removal of solid tumours

Abstract: BackgroundThe gut microbiome has emerged as a promising innovative therapeutic target for immune-stimulation treatment of solid tumours. MRx0518 is a novel, gut microbiome-derived oral live biotherapeutic. It has potent anti-tumorigenic efficacy in the preclinical setting including murine models of lung (LLC1), kidney (Renca) and breast (EMT6) cancer.1 In these models, a significant reduction in tumour growth has been demonstrated, including induction of immunostimulatory responses with tumour infiltration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In one of the trials, MRx0518 was used as monotherapy in the neoadjuvant setting for multiple solid tumors (NCT03934827). Results from part A of the study showed safety and tolerability of MRx0518, and exploratory analyses of post-treatment samples demonstrated increased infiltration of immune cells [ 90 ]. In another trial, MRx0518 was used in combination with pembrolizumab in patients with advanced solid tumors refractory to ICIs (NCT03637803).…”
Section: Current Clinical Trialsmentioning
confidence: 99%
“…In one of the trials, MRx0518 was used as monotherapy in the neoadjuvant setting for multiple solid tumors (NCT03934827). Results from part A of the study showed safety and tolerability of MRx0518, and exploratory analyses of post-treatment samples demonstrated increased infiltration of immune cells [ 90 ]. In another trial, MRx0518 was used in combination with pembrolizumab in patients with advanced solid tumors refractory to ICIs (NCT03637803).…”
Section: Current Clinical Trialsmentioning
confidence: 99%
“…1 We have previously shown MRx0518 therapy is associated with significant anti-tumorigenic genomic, cytokine and immune modulatory changes in treatment-naïve cancer patients. 2,3 Here, we report compositional taxonomic and metabolomic changes following MRx0518 treatment. Methods NCT03934827 is a Phase 1B single-centre study in patients with histologically confirmed cancer undergoing surgical resection.…”
mentioning
confidence: 97%